Digital Marketing And Customer Value In Driving E-Commerce Platform Selection Decisions: Evidevce From Food SMEs - Mahnun Mas'adi; Umi Narimawati; Popo Suryana (International Journal of Social Sciences, 2026)
This research is motivated by the phenomenon of digital transformation challenges for food MSMEs who often face obstacles in determining the right e-commerce platform for long-term business growth. The purpose of this study is to analyze the influence of digital marketing on customer value and its implications for the decision to choose an e-commerce site for food MSMEs participating in the Go Online program in the Greater Tangerang area. The research method uses a quantitative approach with an explanatory survey method of 370 respondents who are MSME owners or managers. Data analysis was conducted using Structural Equation Modeling (SEM) with LISREL 8.80 software. The research findings show that digital marketing has a positive and significant effect on customer value with an influence contribution of 24.90%. Furthermore, customer value is proven to be the main determinant that dominantly influences the decision to choose an e-commerce site with a coefficient of determination of 82.37%. The conclusion of the study confirms that the effectiveness of digital marketing strategies plays a crucial role in shaping value perceptions, which then becomes the most critical consideration for MSMEs in choosing a digital platform. The implications of this research suggest that e-commerce platform managers improve supporting features that can create added value for users, as well as for MSMEs to optimize the use of digital media to increase competitiveness and business value in the digital economic ecosystem.